Low Density Polyester Particles As Lightfillers For Wood-based Panels - Luísa Carvalho (2014)
This work studies the synthesis of low density particles (LDPs)based on crosslinked polyester, each particle containingnumerous air-filled vesicles. Due to its particular internalstructure and rigidity they can be used as fillers in wood-basedpanels to reduce the final density and keep their desiredmechanical performance. Important process variables as stirringconditions, type of cure initiator and drying conditions werestudied. Particles well vesiculated and with diameters in therange 1- 4 mm were prepared and its performance in wood-basedpanels is an on-going study.